If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 5y = 60 Solving -12x + 5y = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -12x + 5y + -5y = 60 + -5y Combine like terms: 5y + -5y = 0 -12x + 0 = 60 + -5y -12x = 60 + -5y Divide each side by '-12'. x = -5 + 0.4166666667y Simplifying x = -5 + 0.4166666667y
| 4-.4x=.2x-8 | | 3x(2x+4)=6(5x+2) | | 8w+3-10w= | | 2w-11w=-12 | | 7.9=2n-5 | | y+y+x+39=180 | | X+X+10=56 | | 25a^3+20a^2+3a= | | 7x-12=4x-9 | | 131/3x2/3 | | x-5/4-x-4/5=1/2-x/10 | | 4.8=2.1-0.5y | | 1/4×20 | | 4.7=2.4-0.7y | | N-3=15/5 | | 4(5x+2)=100+8 | | f(x)=3x-1/2x^2 | | f(x)=3x-1/x^2 | | f(x)=-8ex+7x-4 | | 110a+30=90-10a | | (6+2x)(11+2x)=94 | | 3q+2q+q-6q+2q=18 | | 9a-15=39 | | 5/2/50=x/80 | | 3x-4=0.5x+7 | | f(x)=3x*ln(3x) | | 9x-136+6x-76=180 | | 12k-10k+4K+4K=20 | | 15=3/8w | | (5*x)/10=-7/(3*x) | | 2n^2+4n+6=4 | | 1/3÷5/6 |